Analisis Resepsi Generasi Z Surabaya Terhadap Standar Kecantikan Pada Laki-laki Dalam Iklan MS GLOW FOR MEN - Malafitri, Novreza; Zuhri, Saifuddin; Achmad, Zainal Abidin (Universitas 17 Agustus 1945 Surabaya, 2022)
This study discusses the reception of Generation Z in Surabaya on male beauty standards in Babe Cabita and Marshel Widianto's version of the MS Glow For Men advertisement. The advertisement shows a concept of a different male beauty standard, using Babe Cabita and Marshel Widianto, who are known as leading comedians in Indonesia with tan skin, curly hair, short stature, and fat, as beauty product advertising models, MS Glow For Men. In addition, at the beginning of the commercial video scene, professional figures have never been seen in beauty product advertisements, including construction workers, online motorcycle taxi drivers, and tire repairmen. This attracted the interest of researchers to find out how Surabaya's Generation Z accepted the concept displayed in the advertisement. This study uses a qualitative research method with Stuart Hall's reception analysis theory. The number of research informants was 7 people. Data collection techniques used are interviews and documentation. The results showed that each informant had a different reception. The interpretation comes from the knowledge and experience gained by the informants from everyday life. Keywords : Male Beauty Standard, Advertising